ANALYSIS OF THE IMPLEMENTATION OF CONSUMER PROTECTION LAWS IN INDONESIA - Santy (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This research aims to analyze the implementation of consumer protection law in Indonesia by highlighting various aspects that influence its effectiveness. Using a literature study method, this research explores the role of law enforcement, industry and business compliance, and the use of digital technology in an effort to provide optimal protection to consumers. The research results show that the understanding and capacity of law enforcement needs to be improved in order to handle cases fairly and professionally. On the other hand, business actors must maintain their commitment to product regulations and transparency for the sake of consumer safety. Apart from that, digital technology has been proven to have great potential in making it easier for consumers to get information and report violations in real- time. The conclusion of this analysis shows that collaboration between government, society and the private sector is very necessary to create a more modern and efficient consumer protection ecosystem in Indonesia.